Implementation of the right to food and the poverty reduction papers in perspective: the Ethiopian and the South African examples - Rose-Sender, Kate (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2003.